2011
DOI: 10.1074/jbc.m110.199448
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine Oxidation within N-terminal Mutant Huntingtin Promotes Oligomerization and Delays Clearance of Soluble Protein

Abstract: Huntington disease (HD) is a progressive neurodegenerative disorder caused by expression of polyglutamine-expanded mutant huntingtin protein (mhtt). Most evidence indicates that soluble mhtt species, rather than insoluble aggregates, are the important mediators of HD pathogenesis. However, the differential roles of soluble monomeric and oligomeric mhtt species in HD and the mechanisms of oligomer formation are not yet understood. We have shown previously that copper interacts with and oxidizes the polyglutamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 44 publications
1
42
0
2
Order By: Relevance
“…One possibility is that systemic influences, such as oxidative stress or inflammation, could concordantly modulate brain pathology and cause peripheral changes such as Htt oligomerization and aggregation. 30 The increase in plasma levels of the DNA damage marker 8-OH2dG that occurs as clinical symptoms develop is consistent with this possibility. 31,32 We have also described gene expression changes in leukocytes that indicate progressive influences on them from HD.…”
Section: Results Demographic and Experimental Characteristicssupporting
confidence: 61%
“…One possibility is that systemic influences, such as oxidative stress or inflammation, could concordantly modulate brain pathology and cause peripheral changes such as Htt oligomerization and aggregation. 30 The increase in plasma levels of the DNA damage marker 8-OH2dG that occurs as clinical symptoms develop is consistent with this possibility. 31,32 We have also described gene expression changes in leukocytes that indicate progressive influences on them from HD.…”
Section: Results Demographic and Experimental Characteristicssupporting
confidence: 61%
“…Previous studies have demonstrated that disulfide bridges formed by active cysteines contribute to oligomerization of some proteins including disease-related Huntingtin [21], membrane-bound transcription factor [22], and glucan phosphatase family members [23]. eEF1A1 contains six well-conserved cysteine residues located in different domains ( Fig.…”
Section: Specific Cysteines Are Responsible For the Recombinant Eef1amentioning
confidence: 99%
“…For that purpose, an endoproteinase, Glu-C, was used for a limited proteolysis of HTT EX1 , which can produce a relatively small proteolytic fragment (Lys 6 -Glu 12 ) that contains Met 8 but not a polyQ tract. To test whether digestion of HTT EX1 with Glu-C produces a Lys 6 -Glu 12 peptide, in vitro aggregates of HTT EX1 (42Q) before Met 8 oxidation were resolubilized with TFA, incubated with Glu-C and then analyzed with MALDI-TOF mass spectrometry (see "Experimental Procedures"). As shown in Fig.…”
Section: Met 8 Of Htt Is Oxidized In the Pathological Aggregates Of Hmentioning
confidence: 99%
“…A copper ion functions as a pro-oxidant and is suggested to oxi-dize cysteine residues to form disulfide-linked HTT oligomers (12). Given that almost all of mutant HTT proteins are already aggregated at the disease end stage, however, the aggregation model triggered by oxidative modification on soluble HTT proteins seems questionable.…”
mentioning
confidence: 99%